Iodine-catalyzed Sulfonylation of Arylacetylenic Acids and Arylacetylenes with Sodium Sulfinates: Synthesis of Arylacetylenic Sulfones - Jatuporn Meesin (2018)
© 2016 American Chemical Society. A highly efficient and generally applicable iodine-catalyzed reaction of arylacetylenic acids and arylacetylenes with sodium sulfinates for the synthesis of arylacetylenic sulfones was developed. The methodology has the advantages of a metal-free strategy, easy to handle reagents, functional group tolerance, a wide range of arylacetylenic acids and arylacetylenes, and easy access to arylacetylenic sulfones. (Chemical Equation Presented).